Sobre corporalidad, visión y procesos noéticos en los Hermetica y ciertos paralelos platónicos - Cano Cuenca, Jorge (2025)
“On Corporeality, Sight and Noetic Processes in the Hermetica and Certain Platonic Parallels”. Based on treatises I and XIII of the Corpus Hermeticum (“Poimandres” and “On a Mountain: An Esoteric Discourse Concerning Palingenesis and the Requirement of Silence”) and Nag Hammadi VI (“The Ogdoad and the Ennead”), this article addresses the physical (bodily and sensorial) conditions necessary for Hermetic revelation and how the role played by sensible vision as an opening to a fully noetic dimension has its roots in Plato’s theory of vision. Although what the Hermeticists understand by knowledge is not so much an argumentative and rational learning as a transformative, directly relational and unitive experience (Hermetic gnosis), a clear parallel can be established with the function of the Sun, light and the fiery nature of the eye in key passages of Phaedrus, Republic and Timaeus.